Pola Kemampuan Literasi Digital Guru: Menelaah Kesenjangan Literasi Digital dari Perspektif Gender - Kharisma Salsabila, Chika; Wachidah, Kemil (University of Muhammadiyah Malang, 2024)
This research examines the digital literacy skills of elementary school teachers from a gender perspective, comparing male and female teachers in their implementation of digital literacy in learning activities at SD Muhammadiyah 1 Sidoarjo. SD Muhammadiyah 1 Sidoarjo has integrated digital technology into its learning activities, in line with its slogan,